Electronic theses and dissertations : (Marcel Dekker, 2004)
Examining how electronic publication of theses and dissertations might enhance graduate education, this text clarifies the composition, evaluation, dissemination, and preservation of electronic theses and dissertations (ETDs)—providing a conceptual framework for the development of effective ETD programs and identifying the main technical concerns related to the adoption of ETD initiatives.